Is the expression 2f + 4f + 2 – 3 equivalent to 6f – 1? 6f – 1 evaluated at f = 9 is 53. 2f + 4f + 2 – 3 evaluated at f = 9 is also 53. 6f – 1 evaluated at f = 3 is 17. what is 2f + 4f + 2 – 3 evaluated at f = 3?
the expression 2f + 4f + 2 – 3-------> we can group it (2f+4f)+(2-3) (2f+4f)+(2-3)=(6f-1) therefore the expression [2f + 4f + 2 – 3] is equivalent to [6f-1]
if the expression [6f-1] for f=3 is 17 then the expression [2f + 4f + 2 – 3] for f=3 is also 17
let's check it [2*3 + 4*3 + 2 – 3]--------> [6+12+2-3]=[20-3]=17------> is ok